#### Factor quadratic x^{2} - 3x + 2 with other leading coefficients

Anonymous

0

Sangeetha Pulapaka

0

STEP 1: Recall what is a quadratic

https://www.qalaxia.com/viewDiscussion?messageId=5cea2682f31e6e22f6b0f134

STEP 2: Recall on how to factor a quadratic

https://www.qalaxia.com/viewDiscussion?messageId=5d12c6cf7ae99744ef6d34e1

STEP 3: Recall on how to factor a quadratic by grouping

https://www.qalaxia.com/viewDiscussion?messageId=5cde951735cb1865a389533b

STEP 4: Factor the quadratic

Multiply a * c

In the example a = 1 and c = 2, so ac = 2

Find the two factors of a*c that add up to b.

So, factors of 2 can be -1 and -2, because adding up they are -1 -2 = -3

So the quadratic x^{2} - 3x + 2 can be written as

x^{2} -2x -x + 2

x( x - 2) - 1 ( x - 2)

(x-1)(x-2)